Open to Open? An Exploration of Textbook Preferences and Strategies to Offset Textbook Costs for Online Versus On-Campus Students - Anderson, Talea; Cuttler, Carrie (International Review of Research in Open and Distributed Learning, 2020)
As open textbook initiatives are on the rise, a burgeoning literature has begun exploring student perceptions of openly licensed textbooks used in higher education. Most of this research has lacked consideration of potential differences in the perceptions of online and on-campus students and has failed to include a control group of students using traditional textbooks. Therefore, the authors employed a 2 x 2 design to directly compare perceptions of online students with on-campus students assigned either open or traditional textbooks. Students (N = 925) enrolled in multiple sections of psychology courses at a midsized R1 institution completed a survey on their perceptions of their particular book’s format and features, as well as strategies they typically employ to offset the cost of expensive course materials. The results revealed that online and on-campus students report disparate strategies for offsetting the high costs of textbooks, different preferences in textbook formats (print versus digital versus both) when cost is not a factor, and differences in their ratings of the importance of various textbook features. Moreover, the results indicate that the use of open textbooks may increase preference for free digital textbooks over paid printed textbooks. Based on these results, the authors suggest that campuses might consider providing customized support to different student populations as open textbook initiatives gain in popularity on university campuses. Additionally, they suggest that prior exposure to open textbooks may increase students’ willingness to use openly licensed materials in future courses. They recommend future research on this question, using a longitudinal within-subjects designs.